Progressive Methods of Finishing the Dovetail Grooves of Aircraft Engine Compressor Disc - Tryshyn, Pavlo; Pavlenko, Dmytro; Honchar, Natalia; Khavkina, Olena (International Journal of Integrated Engineering, 2025)
The paper analyses the causes of compressor disc failures in aircraft engines. The high-pressure compressor discs were made of a nickel-based heat-resistant alloy, HN73MBTYu-VD. The complexity of the rim profile and the high level of loads create conditions for the development of fatigue cracks. Fractographic analysis of fractures has shown that the most dangerous cracks occur in the sharp corners at the base of the intergroove protrusions, which can lead to the tearing off of disc parts. The purpose of this study was to evaluate the effect of the optimal combination of finishing the groove forming surfaces on the safety factor of the rim elements of high-pressure compressor discs. Residual stresses were investigated by the layer-by-layer removal of thin metal layers using electrochemical polishing of the groove bottoms. To determine the stresses arising in the acute angle zone of the groove, the finite element method was used. The endurance limit of the specimens was determined after 2×10⁷ loading cycles. It has been established that the optimal combination for the finishing stage of disc manufacturing includes sequential treatment with polymer-abrasive brushes, hardening with steel balls in an ultrasonic field, and pneumatic blasting with glass microbeads. Finish-hardening treatment improved resistance to fatigue crack nucleation by creating a certain depth of plastic deformation in the surface layer, inducing significant compressive residual stresses, improving surface roughness, and increasing microhardness. After this treatment, the safety factor of high-pressure compressor discs increases by 1.8 to 3 times. The paper presents a model for the safety factor of compressor discs with dovetail grooves, which takes into account technological residual stresses and operating conditions.